Pendidikan Karakter Untuk Anak Balita Dengan Mengajarkan Budaya Sopan Santun - Sirana Mikelvania Baby Panjaitan; Emi Triani (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Children are the nation's next generation who are expected to have good character and morals. But unfortunately, as time goes by many children have less good character. This can be a problem because it can cause moral decay for the nation's future generations. Through Field Work Practicum Activities II, the author observes and designs programs for character development that will be applied to children, especially toddlers. Remembering that early childhood is a golden period where the process of growth and development is rapid in all aspects of life. This activity was carried out at UPTD. Medan Social Services for Toddlers, North Sumatra Province Social Service. The implementation of this program uses the social groupwork method to determine student development, including (1) Preparation, (2) Intake and contract, (3) Assessment, (4) Planning, (5) Intervention, (6) Evaluation, and (7) ) Termination.